Shear Characteristics and Strength Criterion of Frozen Joints under Different Opening Degrees - Shiwei Shen; Lin Gan; Chang Liu; Shulin Dai (Advances in Civil Engineering)
Samples of rock coupling joints were collected from the Jiangluling Tunnel of the G214 line in Qinghai province. Models with surface topographies similar to these joints were manually created. Freezing shear tests under different normal stress conditions were conducted to study the shear mechanical properties of these models. On this basis, the integral form of the peak shear strength criterion of frozen joints was proposed. Results show that the shear process of the ice layer can be divided into four stages, namely, initial deformation, continuously increasing shear stress, ice shearing, and residual shear. During the continuously increasing shear stress stage, the stress-strain curve is concave, and elastic deformation is not evident. Furthermore, the increase rate of shear stress generally rises as normal stress intensifies. In the ice shearing stage, shear stress does not decrease instantaneously, but plastic deformation is now detectable. When the opening degree is greater than the undulation difference of the joint surface under the action of all levels of normal stress, the shear stress in the ice sharply increases and drops due to local failure and reicing. Then, evident difference between the shear processes under freezing and normal temperature conditions was then obtained. On this basis, the failure forms of joint surfaces, theory of ice adhesion strength under different opening degrees and morphologies, and the shear failure forms of frozen joints under different conditions were considered. The integral form of the peak shear strength criterion of frozen joints was proposed. These results can lay a theoretical foundation for the stability analysis of rock mass engineering in permafrost areas.